IOT Based Smart Farming for Effective Utilization of Water and Energy - K.N.Sivabalan, V.Anandkumar, S.Balakrishnan (International Journal of Advanced Science and Technology, 2020)
Water is one the precious natural resource which has been over exploited by mankind in the ruthless fashion. As a result this nonrenewable resource is getting exhausted to a drastic extent and nearly 40% of earth population is facing acute water shortage. Nearly 55% of fresh water has been used for agricultural and its allied industries. So we propose a suitable method which uses the blend of technologies to effectively utilize this resource and to enhance the production of agriculture products and eventually minimize the consumption of electrical energy. This project uses raspberry pi B model to interact with the sensors and with the motor pump so that both the water and the electrical energy is minimized.